Correlation between rolling noise generation and rail roughness of tangent tracks and curves in time and frequency domains. (June 2016) - Sadeghi, Javad; Hasheminezhad, Araz
Abstract: Despite considerable advantages of the railway track over other means of transportation, noise pollution is the main adverse consequence of railway transportation. The basic cause of railway noise is rail corrugation. Although characteristics of railway noise have been considerably studied in the literature, rail corrugation effects on rolling noise generation in tangent tracks and the curves have not been sufficiently investigated. This research addresses the limitations of the current understanding of the rolling noise generation by investigating rail corrugation effects on rolling noise in tangent tracks and curves. This research was made based on the results obtained form a thorough field investigation carried out in a railway line which includes tangents tracks and sharp curves. A track geometry recording car was used to measure rail corrugations. For this purpose, an indirect method was developed in this research to obtain rail corrugation patterns from the data recorded by the track recording car. The effectiveness of the new method was shown. The induced noises were recorded using two particular types of microphones and implementing the method suggested by the ISO 3095 Standard. The rolling noise signal was distinguished from the total noise, using Butterworth Band-Pass Filtering. The role of rail corrugations in the rolling noise was discussed. Correlations were made between various types of corrugations and the induced noises. The results were presented and discussed in the spatial and frequency scales. Results obtained have led to new findings in rail corrugation effects on rolling noise generation. This research paves a way toward a better understanding of rolling noise sources and the parameters influencing the noise.